2021
DOI: 10.1155/2021/9376711
|View full text |Cite
|
Sign up to set email alerts
|

Probability Integral Method Parameter Determination by SBAS‐InSAR Technology and GWO Algorithm

Abstract: This paper proposed a method based on the SBAS-InSAR and gray wolf optimization algorithm aiming at the time-consuming and laborious defects of the traditional method used to obtain the expected parameters of the probability integral method and the shortcomings of the InSAR technology in the field of large gradient deformation detection in the mining area. The fitness function of the algorithm was established based on the geometric relationship between the radar side imaging and the three-dimensional model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In order to obtain the smallest error between the wrapped phase gradient and the unwrapped phase gradient, calculate k 1 and k 2 , as shown in the formulas ( 6) and (7):…”
Section: Backgrounds Of the Bc Methods And The Mcf Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain the smallest error between the wrapped phase gradient and the unwrapped phase gradient, calculate k 1 and k 2 , as shown in the formulas ( 6) and (7):…”
Section: Backgrounds Of the Bc Methods And The Mcf Methodsmentioning
confidence: 99%
“…When the unit-price of freight is 1, the length of the path is equal to the freight. Let ω 1 = ω 2 = 1 in formula (6), and the value of k is 0 or 1, and the formula (3) is incorporated into the formula (7); then, the formulas (8) and ( 9) are obtained:…”
Section: Improved the Branch-cut Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zha et al [12] successfully applied a genetic algorithm to the probability integral method for parameter inversion, demonstrating notable advantages in terms of accuracy and reliability. Subsequent investigations explored the use of the modular vector method [13][14][15], particle swarm algorithms [16][17][18][19], simulated annealing algorithms [20,21], and others [22][23][24][25][26][27] for parameter inversion within the probability integral method framework, all yielding highly satisfactory results. In a comparative analysis of parameter inversion outcomes using various intelligent algorithms, Han Mei et al [28] confirmed that, with an appropriate choice of initial exploration values, the modular vector method excels in accuracy and reliability when contrasted with other algorithms.…”
Section: Introductionmentioning
confidence: 99%